PERILAKU MAHASISWA UNIVERSITAS LAMPUNG TERHADAP MINUMAN KEKINIAN BERTOPING BOBA DI KOTA BANDAR LAMPUNG - Messyah Karlindah; Yaktiworo Indriani; Teguh Endaryanto (Jurnal Ilmu-Ilmu Agribisnis, 2023)
This study aimed to analyze the behavior of Lampung University students toward contemporary drinks with boba toppings in Bandar Lampung City. This research was conducted at the University of Lampung using a survey method, in which samples were drawn by purposive sampling technique. The research samples were 100 students from the University of Lampung who bought boba drinks in Bandar Lampung City and had made purchases at least twice during the last month. The data of this study was analyzed by descriptive statistics analysis and multiple linier regressions. Data collection was carried out from May to October 2022. The results showed that students bought boba topping drinks because they have already liked the taste. The flavor variant that students bought the most was the brown sugar flavor variant.Â  The average number of purchases based on flavor variant was 3 cups/month.Â  The average frequency of purchases in the last month was 1 to 5 cups/student/month with an average monthly expenditure of IDR77,120.00. Complementary food of boba drinks, income and tastes were significantly affected on the number of purchases of boba drinks by students.Key words:boba drink, expenditure, flavor, purchase